30 years of IJGIS: the changing landscape of geographical information science and the road ahead. Issue 3 (4th March 2017) - Yuan, May
ABSTRACT: The International Journal of Geographic Information Science (IJGIS), established in 1987, is the first academic journal devoted solely to Geographical Information Science (GIS) research. This editorial highlights milestones of the journal development and its influences on the field. IJGIS research articles and special issues have been effective in publishing the state of the art and emerging research accomplishments. In light of the changing landscape of GIS, IJGIS welcome papers on meta-analysis studies, literature reviews, and research foresight. This editorial outlines the underlying thinking and expectations for these papers in future volumes. IJGIS aspires to publish research of high novelty and broad interest that pushes the boundary of fundamental and applied GIS. As an independent, multidisciplinary journal driven by the community of authors, reviewers, and readers, community support is key to realizing the aspiration of a major influence on GIS research.